« Foin de ma barbe, si je n’ t’arrange une djellaba bien à ta taille ! ». Aspects de la dispute en pays berbère - Claude Lefébure (Revue des Mondes Musulmans et de la Méditerranée)
The closed field of insults in verbal cultures is the argument, the oral quarrel. Considering the principal groupings of Berber speeches, the article has a look first at terms conveying the idea of “verbal aggression” and concludes with the observation that, as with many languages, including those of other linguistic groups, insults are similar to the idea “of cutting a skin”. The oral literature insists: a sharp tongue wounds more durably than an iron weapon. Three short texts by speakers originating from Ayt Sadden in Morocco, Ayt Frah in the Aures region and Irjen in Kabylie, are scanned for what they reveal about arguments in Berber society: exchanges of wild words and fixed formulas associated with gestures which convey a threat of physical and moral aggression. The body is omnipresent and the individual is generally associated with his lineage. Some verbal games come with insulting remarks and curses in which the article sees, in the end, an introduction to the domestication of verbal confrontations.